SWI/SNF complex, promising target in melanoma therapy: Snapshot view - Mollapour Sisakht, Mahsa; Amirkhani, Mohammad Amir; Nilforoushzadeh, Mohammad Ali (Frontiers in Medicine, 2023)
Therapeutic strategies based on epigenetic regulators are rapidly increasing in light of recent advances in discovering the role of epigenetic factors in response and sensitivity to therapy. Although loss-of-function mutations in genes encoding the SWItch/Sucrose NonFermentable (SWI/SNF) subunits play an important role in the occurrence of 34% of melanomas, the potential of using inhibitors and synthetic lethality interactions between key subunits of the complex that play an important role in melanoma progression must be considered. Here, we discuss the importance of the clinical application of SWI/SNF subunits as a promising potential therapeutic in melanoma.